The example of coaching in the public sector: a quantitative case study. (2017) - Edwards, Joseph; Snowden, Michael; Halsall, Jamie P.
Coaching has become a key feature in the public sector environment. Since the global financial crisis greater demands have fallen on public sector organisations. Public sector organisations are in an era of value for money and provide excellent customer service. These organisations have put greater demand on their members of staff to perform well constantly. The aim of this paper is to explore the debates on coaching in a public sector environment. The research was carried out by applying a quantitative approach, namely a questionnaire survey. A public sector organisation was selected as the case study. From this research, it was observed that in the public sector organisation that was selected as the case study, employers were positively in favour of a strong dynamic coaching culture.